UNDECLARED WORK OF SOCIALLY EXCLUDED PEOPLE IN LIGHT OF SURVEY RESEARCH - Mariola Szewczyk-Jarocka (Polityki Europejskie, Finanse i Marketing)
Undeclared work is conducted without entering into an official employment relationship. The aim of the research is to present opinions of respondents on the local labor market about work performed outside of an actual contract by socially excluded people. The analysis was conducted using a survey of the opinions of socially excluded people registered at the Municipal Labor Office in the city of Plock. The analysis included the results of surveys received from 350 respondents, including 195 people surveyed using paper questionnaires and 155 people surveyed using a questionnaire posted on the Internet in 2018. The analyses included the distribution of answers to survey question within the entire sample together with verification of the statistical significance between the answers and such variables as: sex, age, education and period of being registered in the Municipal Employment Office.